2006
DOI: 10.1182/blood-2005-07-3032
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin, and not cyclosporin A, preserves the highly suppressive CD27+ subset of human CD4+CD25+ regulatory T cells

Abstract: The immunosuppressive drugs rapamycin and cyclosporin A (CsA) are widely used to prevent allograft rejection. Moreover, they were shown to be instrumental in experimental models of tolerance induction. However, it remains to be elucidated whether these drugs have an effect on the CD4 ؉ CD25 ؉ regulatory T-cell (T REG ) population, which plays an important role in allograft tolerance. Recently, we reported that alloantigen-driven expansion of human CD4 ؉ CD25 ؉ T REG s gives rise to a distinct highly suppressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
154
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(171 citation statements)
references
References 38 publications
12
154
2
3
Order By: Relevance
“…Whether CLL cells can actively induce T regs or whether disease progression in CLL is only a consequence of the given immunologic constitution of a patient cannot be answered by our study. With T regdepleting and T reg -increasing substances in hand, [28][29][30][31] we have the means to test this hypothesis in preclinical tumor models, such as the Tcl1-mouse model for CLL. 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Whether CLL cells can actively induce T regs or whether disease progression in CLL is only a consequence of the given immunologic constitution of a patient cannot be answered by our study. With T regdepleting and T reg -increasing substances in hand, [28][29][30][31] we have the means to test this hypothesis in preclinical tumor models, such as the Tcl1-mouse model for CLL. 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…To do this, we transduced primary human CD4 T cells with a lentiviral vector expressing pim 2 and noted that pim 2 promoted the expansion of CD4 T cells in the presence and absence of rapamycin (data not shown), making it an attractive target to study in Tregs. Studies have shown that the addition of rapamycin at the initiation of a Treg culture preserves the suppressive function of the expanded cells (3,5,8). This suggests that if pim 2 confers rapamycin resistance in Tregs, it should be expressed in resting Tregs.…”
Section: Natural Foxp3-expressing Tregs Constitutively Express Pimmentioning
confidence: 99%
“…These reports dovetail with the clinical observation that immunosuppressed patients treated with rapamycin have increased frequencies of Tregs. 15,16 Intra-epithelial γδ T cells have been described as a distinct subset of T cells with innate properties that bridge the adaptive and innate immune responses. One such population of intra-epithelial γδ T cells resides in the murine skin.…”
Section: Distinct Reliance Of T Cell Subsets On Mtor Signalingmentioning
confidence: 99%